1997
DOI: 10.1128/aem.63.4.1357-1361.1997
|View full text |Cite
|
Sign up to set email alerts
|

Role of 2,4-Diacetylphloroglucinol in the Interactions of the Biocontrol Pseudomonad Strain F113 with the Potato Cyst Nematode Globodera rostochiensis

Abstract: The potato cyst nematode Globodera rostochiensis is an important pest of potato (Solanum tuberosum). Pseudomonas fluorescens F113, which produces 2,4-diacetylphloroglucinol (DAPG), was investigated as a potential biocontrol agent against G. rostochiensis. Exposure of nematode cysts to the pseudomonad, under in vitro conditions or in soil microcosms, almost doubled the ability of the eggs to hatch. The percentage of mobile juveniles was reduced threefold following their incubation in the presence of the pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(70 citation statements)
references
References 18 publications
2
68
0
Order By: Relevance
“…towards plant-parasitic nematode species belonging to the genera Meloidogyne, Heterodera and Rotylenchulus (Gokta & Swarup, 1988;Kloepper et al, 1992;Madamba et al, 1999;Siddiqui & Mahmood, 1999;Insunza et al, 2002;Kokalis-Burelle et al, 2002;Meyer, 2003;Giannakou & Prophetou-Athanasiadou, 2004;Li et al, 2005). Rhizosphere Pseudomonas strains also exhibit diverse pathogenic mechanisms upon interaction with nematodes (Spiegel et al, 1991;Kloepper et al, 1992;Kluepfel et al, 1993;Westcott & Kluepfel, 1993;Cronin et al, 1997a;Kerry, 2000;Jayakumar et al, 2002;Andreogloua et al, 2003;Siddiqui et al, 2005). The mechanisms employed by some Pseudomonas strains to reduce the plantparasitic nematode population have been studied.…”
Section: Rhizobacteriamentioning
confidence: 99%
“…towards plant-parasitic nematode species belonging to the genera Meloidogyne, Heterodera and Rotylenchulus (Gokta & Swarup, 1988;Kloepper et al, 1992;Madamba et al, 1999;Siddiqui & Mahmood, 1999;Insunza et al, 2002;Kokalis-Burelle et al, 2002;Meyer, 2003;Giannakou & Prophetou-Athanasiadou, 2004;Li et al, 2005). Rhizosphere Pseudomonas strains also exhibit diverse pathogenic mechanisms upon interaction with nematodes (Spiegel et al, 1991;Kloepper et al, 1992;Kluepfel et al, 1993;Westcott & Kluepfel, 1993;Cronin et al, 1997a;Kerry, 2000;Jayakumar et al, 2002;Andreogloua et al, 2003;Siddiqui et al, 2005). The mechanisms employed by some Pseudomonas strains to reduce the plantparasitic nematode population have been studied.…”
Section: Rhizobacteriamentioning
confidence: 99%
“…F113, as well as synthetic DAPG, is known to increase egg hatching of the root pathogenic nematode Globodera rostochiensis, but to reduce the mobility of the juveniles [61]. The reduced juvenile mobility suggests that survival conditions are suboptimal, while increased egg hatching would potentially increase nematode attack on plants.…”
Section: Protozoa and Nematodesmentioning
confidence: 99%
“…In one such strain, designated CHA0, hydrogen cyanide (HCN) and 2,4-diacetylphloroglucinol (Phl; Keel et al, 1992) have been shown to be major determinants of the strain's biocontrol ability. HCN and, especially, Phl are also implicated in the biological control of soil-borne phytopathogens by other antagonistic fluorescent pseudomonads (Vincent et al, 1991;Fenton et al, 1992;Keel et al, 1992;Cronin et al, 1997;Ellis et al, 2000;Haas & Keel, 2003;Moënne-Loccoz & Défago, 2004). In addition, Phl 1 pseudomonads and Phl synthesis contribute to the monoculture decline of take-all disease of wheat caused by Gaeumannomyces graminis var.…”
Section: Introductionmentioning
confidence: 99%